ANALYSIS OF ORNAMENTAL PLANT BUSINESS INCOME (CASE STUDY OF HOUSEHOLD BUSINESS DANSHA FLORIST KEC. PACET, CIANJUR) - Junaidi Junaidi; Titik Inayah; Fatma Qolbi Azhari (Syarif Hidayatullah State Islamic University Jakarta, 2021)
Dansha Florist is a household-scale industry that produces a variety of ornamental plants, namely ornamental leaf plants, and flower ornamental plants in Cianjur. However, the demand and production of Dansha florist ornamental plants still fluctuate every month and the average ornamental plant production has not been able to meet consumer demand. Fluctuations in the price of ornamental plants affect the revenue of Dansha Florist's household business. Dansha Florist has not done periodic bookkeeping and evaluation, so the benefits obtained are not visible as a whole. The purpose of this study is to analyze the costs incurred by the ornamental plant business in Dansha Florist, analyze the income of the Dansha Florist ornamental plant business, analyze the level of R/C Ratio, B/C Ratio, Payback Period (PP), and Break Event Point (BEP).The results of this study are costs are incurred in the form of fixed costs such as UN costs, labor costs, and depreciation costs. Operating revenue in 2019 amounted to Rp. 349,199,698,-. The results of the calculation of the analysis of the R/C ratio, B/C ratio, Break Event Point (BEP), and Payback Period (PP): a. The value of R/C ratio is 1.58 and the R/C ratio of the flower ornamental plant business is 1.06. So the condition of the ornamental plant business on Dansha Florist is feasible to run. b. The value of the B/C business ratio of leaf ornamental plants is 0.58 and the B/C ratio to the total cost obtained by the leaf ornamental plant business is 0.06. Then the business is profitable to run. The results of the BEP calculation of the leaf ornamental plant business obtained a volume BEP value of 35,499 pots and the BEP price of Rp. 6,311 per pot. As well as the results of the BEP calculation of the flower ornamental plant business obtained a volume BEP value of 92,280 pots and a BEP price of Rp. 23,554 per pot. The payback value of the leaf plant business period is 1.47 which shows a return on capital for 1 year and 5 months. The payback period of the flower plant business is 2.15 which shows for 2 years and 1 month.